Improving The Student Speaking Skill By Using Tiktok Application - Pujiastuti, Nur Aini (YAYASAN HAMJAH DIHA bekerjasama dengan PENA INSTITUTE, 2025)
This research focuses on speaking skill by using Tiktok Application. This study aims to describe the phenomenon of the widespread use of social media as a learning media English online. This study uses a qualitative method with an inductive approach. The data was collected with documentation from online videos. The research findings show that there are five types of lessons from online video TikTok that are often made, namely pronunciation, vocabulary, grammar, common mistakes, and English fact. The data in this study was analyzed by qualitative. From this research shows that the respondents had a positive attitude toward a TikTok application as a video aid while learning through TikTok application used it as an English language learning strategy to help and enhance literacy and speaking skills.